2006
DOI: 10.1111/j.1365-2893.2006.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological differences between hepatitis B viral genotype B‐ and C‐related resectable hepatocellular carcinoma

Abstract: Clinical and pathogenic differences exist between hepatitis B viral (HBV) genotypes B and C, and genotype C has a higher risk of hepatocellular carcinoma (HCC) development than genotype B. The aim of this study was to investigate whether HBV genotypes B and C influence the clinicopathological features of patients with resectable HCC. Stored serum samples from 193 patients with resectable HBV-related HCC were tested for HBV genotypes by a molecular method. Of 193 patients undergoing resection of HCC, 107 (55%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
(49 reference statements)
4
16
0
Order By: Relevance
“…All these possible mechanisms might explain why higher serum HBV-DNA level was associated with poor prognosis of HCC and became an important risk factor of metastasis or recurrence. Clinical and virological implications of HBV genotypes showed that HBV genotype C has a higher risk of HCC development than HBV genotype B, and genotype C HBV infection may be associated with more active and progressive liver disease [Lin et al, 2007]. A previous pathological study on HCC suggested that patients with genotype C HBV infection could be prone to the development of multiple tumors in cirrhosis liver, and liver cirrhosis and multiple tumors have been documented as important prognostic factors for patients with respectable HCC [Tobe et al, 1994].…”
Section: Discussionmentioning
confidence: 98%
“…All these possible mechanisms might explain why higher serum HBV-DNA level was associated with poor prognosis of HCC and became an important risk factor of metastasis or recurrence. Clinical and virological implications of HBV genotypes showed that HBV genotype C has a higher risk of HCC development than HBV genotype B, and genotype C HBV infection may be associated with more active and progressive liver disease [Lin et al, 2007]. A previous pathological study on HCC suggested that patients with genotype C HBV infection could be prone to the development of multiple tumors in cirrhosis liver, and liver cirrhosis and multiple tumors have been documented as important prognostic factors for patients with respectable HCC [Tobe et al, 1994].…”
Section: Discussionmentioning
confidence: 98%
“…Among our 193 patients with resectable HBV-related HCC, genotype B patients were less associated with cirrhosis compared with genotype C patients (33% vs. 51%, P = 0.01). Pathologically, genotype B patients had a higher rate of solitary tumor (94% vs. 86%, P = 0.048) and more satellite nodules (22% vs. 12%, P = 0.05) than genotype C patients [57]. These characteristics may contribute to the recurrence patterns and prognosis of HBV-related HCC patients with genotype B or C infection [58].…”
Section: Genotype and Subgenotypementioning
confidence: 97%
“…In Taiwan, among 193 HBV-related HCC patients receiving surgery, genotype B patients had a higher rate of solitary tumor (94% vs. 86%, P ¼ 0.048) but more satellite nodules (22% vs. 12%, P ¼ 0.05) than genotype C patients (Chen et al 2004b;Lin et al 2007b). Wu et al (2009) also reported that in HCC patients, liver inflammation activity was higher in HBV genotype C patients than in genotype B patients (P ¼ 0.023), and more genotype C patients tended to have a higher viral load (.10 6 copies/ml) than genotype B patients (52.3% vs. 37.6%, P ¼ 0.067).…”
Section: Hbv Genotypes and Risk Of Hcc Developmentmentioning
confidence: 99%